The Post-Election Violence in Kenya: Domestic and International Legal Responses - Materu, Sosteness Francis (Springer, 2016)
Since the historic Nuremberg Trial of 1945 an international customary law principle has developed that commission of a core crime under international law – war crimes, genocide, crimes against humanity and aggression – should not go unpunished. History shows, that when in Africa such violations occurred, especially as a result of election disputes, national and regional actors, including the African Union, resorted to political rather than legal responses. However, when crimes against humanity were alleged to have been committed in Kenya during the 2007-2008 post-election violence, a promising road map for criminal accountability was agreed upon alongside a political solution.